Salvage Hypofractionated Accelerated Versus Standard Radiotherapy for Biochemical Recurrence After Radical Prostatectomy: A Phase III Randomized Clinical Trial - Youngju Song; Won Park; Hongryull Pyo; Yeon Joo Kim; Hanjong Ahn; Hwa Jung Kim; Young Seok Kim (Journal of Clinical Oncology, 2026)
PURPOSE To compare hypofractionated radiotherapy (RT) with conventional RT for treating biochemical recurrence following radical prostatectomy. METHODS Between 2019 and 2021, 316 patients with intermediate- to high-risk prostate cancer were randomly assigned to receive salvage RT with either 65 Gy in 26 fractions (hypofractionated RT, HYPO) or 66 Gy in 33 fractions (conventional RT, CONV). RT was delivered to the prostate bed, with elective pelvic nodal irradiation performed at the discretion of radiation oncologists. Intensity-modulated RT with daily image guidance was used. The primary end point was biochemical progression-free survival (bPFS). Secondary end points included distant metastasis-free survival (DMFS), prostate cancer–specific survival (CSS), toxicity profiles, and patient-reported quality-of-life. RESULTS One hundred fifty-one patients (51.2%) received androgen deprivation therapy, and 202 (68.5%) underwent elective nodal irradiation. Endorectal balloons were used in 186 men (63.1%). The median pre-RT prostate-specific antigen level was 0.36 ng/mL (IQR, 0.24-0.49 ng/mL). After a median follow-up of 52.6 months, the 4-year bPFS rates were 80.1% and 78.1% in the HYPO and CONV arms, respectively. There were no significant differences in DMFS (91.7% v 91.0%) and CSS (100% v 100%). The 4-year cumulative incidence of grade ≥2 GI toxicity was higher in the HYPO arm (7.9% v 0.7%), predominantly among patients without an endorectal balloon; all cases were resolved by the last follow-up. Patient-reported quality-of-life outcomes were comparable. CONCLUSION bPFS was not superior in the HYPO arm at 4 years. However, given the comparable oncologic outcomes, toxicity profiles, and quality-of-life measures, hypofractionated RT may be considered a viable alternative in the salvage setting. Further research is needed to determine whether the use of an endorectal balloon reduces GI toxicity.